2004
DOI: 10.1590/s0100-40422004000300017
|View full text |Cite
|
Sign up to set email alerts
|

Semicarbazonas e tiossemicarbazonas: o amplo perfil farmacológico e usos clínicos

Abstract: Recebido em 31/7/03; aceito em 24/9/03 SEMICARBAZONES AND THIOSEMICARBAZONES: THEIR WIDE PHARMACOLOGICAL PROFILE AND CLINICAL APPLICATIONS. This article shows that thiosemicarbazones, semicarbazones and their metal complexes can exhibit target selectivity along with a wide pharmacological profile. Complexes of thiosemicarbazones with cytotoxic or antitumoral activity are presented, some of which show activity against cisplatinum-resistant cells. The inhibition mechanism of the enzyme ribonucleoside diphosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
11

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 53 publications
1
47
0
11
Order By: Relevance
“…A obtenção de semicarbazonas e tiossemicarbazonas foi baseada no fato de que compostos contendo tais grupos, freqüentemente, apresentam um amplo perfil farmacológico e constituem uma importante classe de compostos cujas propriedades têm sido extensivamente estudadas em Química Medicinal 30 . Além disso, recentemente, foi demonstrado que 5-nitrofurfural-2-carboxaldeído semicarbazonas (Figura 4) são potenciais inibidores da TR e apresentam considerável atividade tripanosomicida 10,31 .…”
Section: Resultados E Discussão Sínteseunclassified
“…A obtenção de semicarbazonas e tiossemicarbazonas foi baseada no fato de que compostos contendo tais grupos, freqüentemente, apresentam um amplo perfil farmacológico e constituem uma importante classe de compostos cujas propriedades têm sido extensivamente estudadas em Química Medicinal 30 . Além disso, recentemente, foi demonstrado que 5-nitrofurfural-2-carboxaldeído semicarbazonas (Figura 4) são potenciais inibidores da TR e apresentam considerável atividade tripanosomicida 10,31 .…”
Section: Resultados E Discussão Sínteseunclassified
“…Domínios como nanociência e nanotecnologia [11][12][13] , fármacos [14][15][16][17][18] , ambiente [19][20][21][22][23][24][25][26] …”
Section: Publicações Científicasunclassified
“…4 The existence of different possible hypotheses to explain the onset and progression of AD directs the development of new drugs toward molecules with multiple actions that are able to act in a complementary manner and could bring satisfactory results for the treatment of the disease. 11,22 There is considerable interest in thiosemicarbazones because they constitute an important class of compounds whose properties have been extensively studied in Medicinal Chemistry, 23 displaying a wide range of biological activities, such as antiviral, 24 antitumor, 25 antimicrobial, 26 antibacterial and antifungal 27 properties. Moreover, studies show that these compounds have excellent antioxidant activities 27,28 and other authors have reported interesting results of thiosemicarbazones in combating AD.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] Thiosemicarbazones are reported to act as enzyme inhibitors by complexing endogenous metals or by redox reactions and as inhibitors of DNA synthesis through DNA interactions. 23 Furthermore, thiosemicarbazones have been proposed to inhibit cysteine proteases, which are essential to several functions of the malaria parasite. 32 Based on these observations, the aim of this study was to synthesize a series of thiosemicarbazones, four of which had not been reported in the literature before, as potential therapeutic agents for the treatment of AD.…”
Section: Introductionmentioning
confidence: 99%